Portable in practice: investigations using portable instrumentation for materials analysis and mapping of decorated architectural surfaces in the tablinum of the House of the Bicentenary at Herculaneum. (3rd May 2017) - Graves, Kiernan; Carson, David; Catapano, Ilaria; Chiari, Giacomo; Gennarelli, Gianluca; Heginbotham, Arlen; Masini, Nicola; Piqué, Francesca; Sileo, Maria; Rainer, Leslie
ABSTRACT: The conservation of the architectural surfaces in the tablinum of the House of the Bicentenary at the ancient Roman site of Herculaneum is a collaborative project of the Getty Conservation Institute, the Herculaneum Conservation Project and the Soprintendenza Pompeii. The tablinum was selected as a case study given the significance, beauty, and severe deterioration of its decorated surfaces. A multi-disciplinary team with a wide range of expertise, comprised of conservators, chemists, geo-physicists, engineers, and conservation scientists, worked in partnership across a number of institutions with the objective to study the wall paintings in the tablinum. Scientists and conservators worked together to test the feasibility of portable techniques and in situ investigations to better understand Roman painting technology; identify previous restoration materials; determine the presence of alteration products; and characterize deterioration mechanisms commonly found on architectural surfaces at archaeological sites of the Vesuvian Region. The collection and interpretation of the instrumental data has been critical to the design and implementation of appropriate passive and remedial interventions to stabilize the architectural surfaces and mitigate deterioration. The paper will present the results of the investigations using portable instrumentation along with a discussion of the capabilities and limitations of each technique and the practical implications of their use for architectural surfaces on archaeological sites.